PENGARUH POLA ASUH ORANG TUA TERHADAP PERILAKU SOSIAL ANAK USIA DINI DI TK ABA - Evicenna Yuris; Qaulan Raniyah; Rahimah Rahimah (Jurnal Muara Pendidikan, 2023)
The research aims to determine the influence of parenting patterns on the social behavior of young children attending TK ABA 21 and TK ABA 07, Medan City. The problem focuses on the importance of parenting education, especially material about ideal parenting patterns. In order to approach this problem, theoretical references from Baron and Byrne (Habel, 2015) regarding social behavior and Hurlock (1999) regarding parenting patterns are used. Data was collected through a research sample of 50 parents of students from both kindergartens using instruments in the form of a parenting style scale and an early childhood social behavior scale and analyzed quantitatively. This study concludes that there is an influence of parental parenting on early childhood social behavior with an R square value of 0.464, with this value meaning that 46.4% of the variation in early childhood social behavior is influenced by parental parenting. Meanwhile, the remaining 52.5% is influenced by other variables outside this research. Democratic parenting has a positive and significant influence on early childhood social behavior, and authoritarian parenting positively affects early childhood social behavior. Still, it is not statistically significant, and permissive parenting negatively affects early childhood social behavior and is statistically significant.